Higher Education and Social Transformation in South Africa Since the Fall of Apartheid - Thiven Reddy (Les éditions de la Maison des sciences de l'Homme, 2006)
The paper locates post-apartheid developments in higher education in relation to the nature of a transition by 'transplacement' (one of compromise between the old ruling elite and moderate nationalists of the liberation movement). It then discusses the neo-liberal macro-economic context adopted post-1994 and its effect of limiting the state's capacity to transform civil society in terms of its own vision. The third section discusses the key policies concerning higher education transformation. It suggests that the post-1994 policy towards higher education is inevitably open to opposing readings. The final section analyses the relations between higher education and its empirical impact on the economic, political, social, and cultural spheres of post-apartheid society. It concludes that higher education has contributed towards the creation of the emerging black middle class (and in doing so assists in consolidating the democratic gains), but also that state policies and university practice exclude the majority of poor students, displaying the emerging class dynamics of post-apartheid South African society.